2021
DOI: 10.4103/mjdrdypu.mjdrdypu_84_20
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of Liver Function Tests in Acute Malaria with Hepatic Involvement

Abstract: Context: Malaria is one of the major public health problems worldwide with increased morbidity and mortality. India has the fourth highest malaria burden in the world. Malaria parasite affects multiple organs of the body including liver, spleen, brain, kidney, blood vessels etc. Organ dysfunction predominantly seen in Plasmodium falciparum malaria, is not in Plasmodium vivax infections. Aims: The present study investigated the abnormalities of liver fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…On the other hand, serum albumin, globulin, and total protein levels were unchanged. It was reported that high serum bilirubin was the first indicator of liver impairment three days after infection, followed by increased serum aspartate transaminase (AST) and alanine transaminase (ALT) activities ( Bhattacharjee et al, 2021 ) ( Fig. 1B ).…”
Section: Resultsmentioning
confidence: 97%
“…On the other hand, serum albumin, globulin, and total protein levels were unchanged. It was reported that high serum bilirubin was the first indicator of liver impairment three days after infection, followed by increased serum aspartate transaminase (AST) and alanine transaminase (ALT) activities ( Bhattacharjee et al, 2021 ) ( Fig. 1B ).…”
Section: Resultsmentioning
confidence: 97%